2007
DOI: 10.1002/ajpa.20745
|View full text |Cite
|
Sign up to set email alerts
|

Strong postcranial size dimorphism in Australopithecus afarensis: Results from two new resampling methods for multivariate data sets with missing data

Abstract: There is considerable debate over the level of size dimorphism and inferred social behavior of Australopithecus afarensis. Most previous studies have analyzed size variation in single variables or multiple variables drawn from single elements. These approaches suffer from small sample sizes, underscoring the need for new techniques that incorporate measurements from multiple unassociated elements, reducing the influence of random sampling on size variation in fossil samples. One such technique, the template me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 79 publications
(153 reference statements)
2
91
0
4
Order By: Relevance
“…This sampling bias underlies long-standing opposing views. Whereas many observers still argue for a gorilla-like, or even higher level of body size dimorphism, such studies are still highly influenced by Lucy, which contributes disproportionately to their estimates (29). However, when randomization techniques allowing independent and equal contribution of individuals are used, the results show that Au.…”
Section: Dentition Andmentioning
confidence: 89%
“…This sampling bias underlies long-standing opposing views. Whereas many observers still argue for a gorilla-like, or even higher level of body size dimorphism, such studies are still highly influenced by Lucy, which contributes disproportionately to their estimates (29). However, when randomization techniques allowing independent and equal contribution of individuals are used, the results show that Au.…”
Section: Dentition Andmentioning
confidence: 89%
“…afarensis range from c.30 to c.65 kg (Grabowski et al, 2015), known endocranial volumes range between 385 and 550 cm 3 , and estimates of the standing height of adult individuals range between 1.0 and 1.5 m. Reno et al (2003) suggested that skeletal size sexual dimorphism in Au. afarensis is at a relatively low level, but most researchers (e.g., Gordon et al, 2008) have concluded that this taxon shows a substantial level of sexual dimorphism.…”
Section: 0-30 Mamentioning
confidence: 99%
“…The samples are analysed for the determination of their size dimorphism, using MatLab R 2010 and following the statistical analysis procedure of Scott et al [2009]. The authors used the geometricmean-based method of Gordon et al [2008] for the analysis of multivariate dental size dimorphism; the tooth size was represented by the geometric mean (GM) of the mesiodistal (MD) and buccolingual (BL) diameter [GM = (MD × BL) 1/2 )]. The method allows the examination of the overall dimorphism in a series of variables (in our case dental dimensions).…”
Section: Methodsmentioning
confidence: 99%